2007
DOI: 10.1021/ja068633m
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Study of Amyloid Nanocrystals and Fibrils Formed by the Peptide GNNQQNY from Yeast Prion Protein Sup35p

Abstract: Sup35p is a prion protein found in yeast that contains a prion-forming domain characterized by a repetitive sequence rich in Gln, Asn, Tyr, and Gly amino acid residues. The peptide GNNQQNY7-13 is one of the shortest segments of this domain found to form amyloid fibrils, in a fashion similar to the protein itself. Upon dissolution in water, GNNQQNY displays a concentration-dependent polymorphism, forming monoclinic and orthorhombic crystals at low concentrations and amyloid fibrils at higher concentrations. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
230
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(257 citation statements)
references
References 94 publications
24
230
0
3
Order By: Relevance
“…Two research areas in which high resolution MAS experiments have proved especially successful are studies of amyloid fibrils [37,[51][52][53][54][55][56][57] and membrane proteins [42,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. However, in both of these cases, low sensitivity currently limits the information that can be gleaned from the spectra.…”
Section: Dnp Experiments On the Membrane Protein Bacteriorhodopsinmentioning
confidence: 99%
“…Two research areas in which high resolution MAS experiments have proved especially successful are studies of amyloid fibrils [37,[51][52][53][54][55][56][57] and membrane proteins [42,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. However, in both of these cases, low sensitivity currently limits the information that can be gleaned from the spectra.…”
Section: Dnp Experiments On the Membrane Protein Bacteriorhodopsinmentioning
confidence: 99%
“…However, this concentration is similar to that reported to be essential for amyloid formation of the GNNQQNY core segment of yeast prion Sup35. 61 Using different mutants and phosphorylated serine variants, we gained site-specific information on the structure of the different forms of Trpcage and we could outline the aggregation mechanism. The CD and NMR results revealed that the phosphorylation of any of the serine residues destabilizes the native structure leading to a highly dynamic disordered chain (Table 1 and Fig.…”
Section: Ph Dependence Of the Aggregation Of D9s(p) And 13s(p) Trp-camentioning
confidence: 99%
“…Similarly, one can deriveH (2) 2×2 -the second order contribution of term 2 in Eq. (5) with itself (i.e.…”
Section: Second-order Effective Hamiltonian Autocross Termsmentioning
confidence: 99%
“…Autocross terms of the formH (2) j×j yield longitudinal T 10 operators that can be rearranged as combinations of ZQ/DQ fictitious spin operators. More precisely the relevant Hamiltonian can be written as three commuting terms…”
Section: Second-order Effective Hamiltonian Autocross Termsmentioning
confidence: 99%
See 1 more Smart Citation